2007
DOI: 10.1074/jbc.m704032200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mechanism for Substrate Inhibition in Mycobacterium tuberculosis d-3-Phosphoglycerate Dehydrogenase

Abstract: Mycobacterium tuberculosis D-3-phosphoglycerate dehydrogenase undergoes significant inhibition of activity with increasing concentrations of its substrate, hydroxypyruvic acid phosphate. The enzyme also displays an unusual dual pH optimum. A significant decrease in the K i for substrate inhibition at pH values corresponding to the valley between these optima is responsible for this phenomena. The change in K i has an average pK of ϳ5.8 and involves two functional groups that are protonated and two functional g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 14 publications
5
35
0
Order By: Relevance
“…However, the removal of (or a decrease in) substrate inhibition is generally accompanied by reduced catalytic activity in many enzymes including lactate dehydrogenase, 17␤-hydroxysteroid dehydrogenase, D-phosphoglycerate dehydrogenase, sinapyl alcohol dehydrogenase, and tetrahydroquinone dehalogenase (39,(42)(43)(44)(45). Compared with wild-type SalR, the independent F104A and I275A mutants displayed weak substrate inhibition accompanied by similar or even increased reaction velocities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the removal of (or a decrease in) substrate inhibition is generally accompanied by reduced catalytic activity in many enzymes including lactate dehydrogenase, 17␤-hydroxysteroid dehydrogenase, D-phosphoglycerate dehydrogenase, sinapyl alcohol dehydrogenase, and tetrahydroquinone dehalogenase (39,(42)(43)(44)(45). Compared with wild-type SalR, the independent F104A and I275A mutants displayed weak substrate inhibition accompanied by similar or even increased reaction velocities.…”
Section: Discussionmentioning
confidence: 99%
“…2A (39). For sulfotransferases, the crystal structure showed that the substrate adopts a different conformation and binds closer to the cofactor binding site after the cofactor has been desulfated (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…The latter mechanism can be associated with the dehydrogenase residues located both in the substrate and in cofactor binding sites. Recent biochemical studies have demonstrated that substrate inhibition of several dehydrogenases can be significantly reduced or eliminated by single mutations in the enzyme active site, which can be accompanied by a reduction or increase in the reaction rate and usually correlates with a reduction of substrate affinity (increasing K m ) (4,7,10,13). For example, the mutation S163L in human lactate dehydrogenase eliminates substrate inhibition with a minor effect on its turnover rate, whereas in Bacillus stearothermophilus lactate dehydrogenase the D38R mutation reduces substrate inhibition 3-fold (4,14).…”
mentioning
confidence: 99%
“…For dehydrogenases, several molecular mechanisms of substrate inhibition have been proposed, including the formation of a covalent adduct between the oxidized forms of substrate and cofactor, allosteric inhibition (which occurs away from the active site, e.g., in D-3-phosphoglycerol dehydrogenase from Mycobacterium tuberculosis), and the formation of a nonproductive enzyme complex with cofactor and/or substrate (6)(7)(8)(9)(10)(11)(12)(13). The latter mechanism can be associated with the dehydrogenase residues located both in the substrate and in cofactor binding sites.…”
mentioning
confidence: 99%
“…The kinetic parameters (K m , k cat , K is , k cat(i) ) of these three ADHs toward CDOH are summarized in Table 2. In the case of partially uncompetitive inhibition, the reaction rate at a relative high substrate concentration can be simply reduced to a supposed value of V i (Burton et al 2007;LiCata and Allewell 1997). In the current study, the value of k cat(i) , which is the catalytic constant related to V i , was treated as an important parameter for comparing the catalytic efficiency with the existence of substrate inhibition.…”
Section: Kinetic Studymentioning
confidence: 98%